Serotype 10A in Case Patients with Invasive Pneumococcal Disease: A Pilot Study of PCR-Based Serotyping in New Jersey. (January 2015) - Pitts, Samantha I.; Apostolou, Andria; DasGupta, Sarmila; Delgado, Nelson; Kirn, Thomas J.; Montana, Barbara; Tan, Christina; McHugh, Lisa A.
In 2008, the New Jersey Department of Health (NJDOH) identified a 21.1% increase in reported invasive pneumococcal disease (IPD). In 2009, NJDOH piloted nucleic acid-based serotyping to characterize serotypes causing IPD. From April through September, NJDOH received specimens from 149 of 302 (49%) case patients meeting our case definition. An uncommon serotype, 10A, accounted for 25.2% of IPD overall and was identified in 12 counties, but it was associated with one county (rate ratio = 5.4, 95% confidence interval [CI] 2.1, 11.8). NJDOH subsequently conducted a case-control study to assess the presentation of and clinical risk factors for 10A IPD. Case patients with 10A IPD were more likely to have had immunosuppression, asthma, and multiple chronic medical conditions than control subjects had (odds ratio [OR] = 2.6, 95% CI 1.1, 6.3; OR=4.7, 95% CI 1.7, 13.2; and OR=2.3, 95% CI 1.0, 5.2, respectively). State-based pneumococcal serotype testing identified an uncommon serotype in New Jersey. Continued pneumococcal serotype surveillance might help the NJDOH identify and respond to future serotype-specific increases.